2001
DOI: 10.1086/324430
|View full text |Cite
|
Sign up to set email alerts
|

Protection against ExperimentalStaphylococcus aureusArthritis by Vaccination with Clumping Factor A, a Novel Virulence Determinant

Abstract: The importance of the fibrinogen-binding adhesin clumping factor A (ClfA) in the pathogenesis of Staphylococcus aureus septic arthritis was examined in an animal model. The protective effect of active and passive immunization with ClfA also was investigated in S. aureus infection models. The severity of arthritis was markedly reduced in mice challenged intravenously with a clfA mutant, compared with mice infected with the wild-type strain. Mice immunized with recombinant ClfA and challenged with S. aureus deve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
202
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 255 publications
(210 citation statements)
references
References 29 publications
8
202
0
Order By: Relevance
“…Some of these proteins were recognized by sera from infected patients and were also found to be associated with clinically invasive disease but their functions remain to be elucidated. One or more of these proteins could be suitable for development as vaccine candidates, alongside the current contenders ClfA (Josefsson et al, 2001) and Cna (Nilsson et al, 1998;Visai et al, 2000). …”
Section: Discussionmentioning
confidence: 99%
“…Some of these proteins were recognized by sera from infected patients and were also found to be associated with clinically invasive disease but their functions remain to be elucidated. One or more of these proteins could be suitable for development as vaccine candidates, alongside the current contenders ClfA (Josefsson et al, 2001) and Cna (Nilsson et al, 1998;Visai et al, 2000). …”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that ClfA is involved in the pathogenesis of experimental endocarditis (Moreillon et al 1995;Entenza et al 2000). ClfA is also involved in causing arthritis in mice (Josefsson et al 2001), and impedes phagocytosis of S. aureus by macrophages (Palmqvist et al 2004). Both ClfA and ClfB bind and activate platelets, through fibrinogen-dependent and fibrinogen-independent pathways, which may have an impact on the pathogenesis of invasive disease (O'Brien et al 2002a).…”
Section: Factors Involved In Adhesion To Host Cellsmentioning
confidence: 99%
“…However, the traditional vaccine available for mastitis (Chang et al, 2008;Middleton, 2008) is rather ineffective due to the fact that animal is lack of immune response to new infections (Reid and Szymanski, 2010). It has been suggested that vaccine produced from the combinations of antigens including CPs and adhensins would be an effective way against bovine mastitis caused by S. aureus (Lorena et al, 2008;Josefsson et al, 2001), but little information is available in this area.…”
Section: Introductionmentioning
confidence: 99%